1933
DOI: 10.3181/00379727-30-6792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nephrectomy on Duration of Action of Barbitals

Abstract: Fitch and Tatum' have divided the barbitals into 2 groups based upon the duration of their action and upon the manner in which they cause death. They found that the longer acting barbitals (especially phenobarbital and barbital, ethyl-n-butyl barbital (neonal), isoamyl barbital (amytal) , ethyl iso-propyl barbital (barbituric acid of ipral) , and also iso-propyl brornallyl barbital (noctal) cause death from pulmonary oedema, while the other barbitals, which they group as the short acting barbitals, when inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1941
1941
1959
1959

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similarly, Hirschfelder and Haury (1933) found that bilateral nephrectomy markedly increased the effect of phenobarbitone in rabbits. These and other workers, therefore, consider that soluble phenobarbitone is eliminated through the kidney and not detoxicated to a significant extent by the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hirschfelder and Haury (1933) found that bilateral nephrectomy markedly increased the effect of phenobarbitone in rabbits. These and other workers, therefore, consider that soluble phenobarbitone is eliminated through the kidney and not detoxicated to a significant extent by the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of elimination was 18-25 % per 24 h and it was about 75 % per 24 h in rats (3,7). Functioning kidneys seem to be essential for the detoxification of phenobarbital (12). Eleven to twenty-five per cent of the dosage given are excreted unchanged in the urine (for references see 20).…”
Section: Findings In Animal Experimentsmentioning
confidence: 99%
“…Most of the phenobarbital is converted to an inactive compound, 5-ethyl-5-(p-hydroxyphenyl) barbituric acid which appears in the urine of dogs as the glucuronide (4, 5). Functioning kidneys seem to be essential for the detoxification of phenobarbital (12).…”
mentioning
confidence: 99%